Analysis of Scientific Topics Published by Jordanian Academics and How to Establish A Unified List of Targeted Periodicals - Obeidat , Othman (Dirasat: Educational Sciences, 2021)
The study aims to show the need for new and modern tools of navigation that are efficient to search in the large quantities issued from the daily titles of scientific research. In addition to, describing modern methods of the journal selection mechanism based on the reference citation analysis system. To evaluate the proposed methods, lists of periodicals names were developed and provided to academic institutions and universities in Jordan to participate in them. It follows the methodology of bibliometric analysis systems that enable comparison to obtain the desired results in more efficient, effective and speedy ways when retrieving information from databases. Various approaches are used to evaluate scientific journals, where the synthesis is more appropriate and ideal. The data was processed by the SPSS program and commercial software familiar to the researcher is also free. Lists of articles for researchers at academic universities were extracted from the databases they share. The references were retrieved from the articles and analyzed using comments and concluding observations or what is called a footnote (EndNoteWeb) and other software such as (SciMAT). The results indicated that the available tools could be combined to obtain a new prototype for further bibliometric analysis studies. To use keywords plus a new impetus has been given to using keywords. Lists of the names of the periodicals that were formed were analyzed on the basis that the articles contain the same sequence of keywords as they were in the authors' papers in the Jordanian academic institutions.